CLINICAL INTERCURRENCIES ASSOCIATED WITH HYALURONIC ACID IN LIP FILLERS, THEIR PREVENTIONS AND TREATMENTS: A NARRATIVE REVIEW OF THE LITERATURE - Talarico Folco, Mariela; Teruo Suguihara, Roberto; Pilon Muknicka, Daniella (Health and Society, 2024)
Introduction First isolated by Karl Meyer and John Palmer in 1934, but described only in 1970 by Laurent, Hyaluronic acid has become a source of several researches in biochemistry as a potential molecule for dermal restructuring and filling in the specialty of Orofacial Harmonization, and like any other substance injected into the human body, is capable of causing, although infrequent, the so-called adverse events. Objective The objective of this narrative review is to report the main adverse effects associated with the use of Hyaluronic acid, as well as its prevention and treatment. Methodology A bibliographic survey was carried out in the Scielo, PubMed and LILACS databases with the following terms: “Hyaluronic acid” and “adverse events”, and by crossing the Boolean descriptors <and> and <or>, the relationship between expressions. Results There was little reference in the literature regarding the frequency of adverse events associated with the use of Hyaluronic acid, but despite being little present, the professional’s knowledge, about how they occur, how to prevent and treat them, is necessary for the clinical practice of the dental surgeon specialized in Orofacial Harmonization.